BUILDING RESEARCH COMPETENCE OF PHD STUDENTS: AN ANALYSIS OF EXPERIENCE OF A PHD SCHOOL - T. А. Strokova (Образование и наука)
Introduction. Postgraduate education of the Russian higher school is traditionally considered as a strategic reserve, which provides the continuity of academic and teaching personnel and the efficiency of education of future experts. However, the total number of this key resource of the higher education system, which guarantees its stable functioning and further forward development, has been reduced in recent years. Postgraduate admission has decreased, in particular, pedagogical training programmes. What is most important, the PhD student quality has substantially dropped.The aim of the present publication was to identify the level of research skills of PhD students of pedagogical specialisation and present the most productive ways for the formation of skills to carry out research activities.Methodology and research methods. The study was based on the ideas of systemic-activity approach, competency-based approach and major provisions of the theory of action. Scientific publications on research projects of PhD students and the concept of “new” post graduate school in the Russian education were analysed. Online survey and questionnaire survey of PhD students, their supervisors and members of dissertation boards were conducted. The assessment of results of research conducted by PhD students, synthesis and description of productive teaching practices and positive pedagogical experience gained at Tyumen State University (TSU) were applied.Results and scientific novelty. Based on the classical interpretation of nature and contents of human activity, a definition of research activity is formulated. It constitutes as the grounds for development of the contents and procedure for the list of research tasks for PhD students to master in order to successfully complete their PhD studies (as yet, the similar register has been compiled and scientifically based only for a bachelor degree). Insufficient competence of many PhD students to organise and conduct an independent scientific and pedagogical search is proved. Unstable components of their research competence are revealed: inability to use the most important elements of the methodology corpus and problems in writing scientific texts. Practically verified methods and means to develop the research competence of PhD students, doctoral candidates, applicants on academic degrees and their research supervisors are described: methodological seminars of the education department, a group analysis of scientific texts for publication, group visits and discussion of open lectures and seminars for teachers of the education department and PhD students, role mini-plays, public preliminary dissertation defense, participation in the events held by the department, etc.Practical significance. Knowledge of the gaps in research competence of PhD students will allow their supervisors to selectively improve the students’ skills, which are necessary for writing and defending the dissertation. Creative application and systematically scientific-pedagogical work will help achieve a significant improvement in building PhD student competence for scientific and teaching activities.